SOCIAL IMPACT ON THE EXISTENCE OF LAYING CHICKEN FARMING IN BATANG DISTRICT JENEPONTO REGENCY - Syahrini S; Abd Halil; Nurdin (Universitas Muhammadiyah Makassar, 2026)
This study aims to examine the social impacts of the existence of layer chicken farms in Batang District, Jeneponto Regency. This research employed a descriptive qualitative approach. Informants were selected using a purposive sampling technique based on criteria relevant to the research objectives. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing techniques. The results indicate that the presence of layer chicken farms has both positive and negative social impacts on the surrounding community. Positive impacts include the creation of employment opportunities, increased community income, the growth of supporting businesses, and the utilization of livestock manure as organic fertilizer for sustainable agriculture. Negative impacts include unpleasant odors, noise, increased fly populations, and social conflicts between farmers and local residents. The study also reveals that while layer chicken farming contributes to local economic development, effective environmental management and good communication between farmers and the community are essential to minimize negative impacts. Sustainable farm management is therefore important to achieve a balance between economic benefits, social well-being, and environmental sustainability.